2017
DOI: 10.1002/jcp.25912
|View full text |Cite
|
Sign up to set email alerts
|

Knockout of ATG5 leads to malignant cell transformation and resistance to Src family kinase inhibitor PP2

Abstract: Autophagy can either promote or inhibit cell death in different cellular contexts. In this study, we investigated the role of autophagy in ATG5 knockout (KO) cell line established using CRISPR/ Cas9 system. In ATG5 KO cells, RT-PCR and immunoblot of LC3 confirmed the functional gene knockout. We found that knockout of ATG5 significantly increased proliferation of NIH 3T3 cells. In particular, autophagy deficiency enhanced susceptibility to cellular transformation as determined by an in vitro clonogenic surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…The use of CRISPR/Cas9‐mediated ATG5 knockout can significantly promote cell proliferation of the mouse embryonic fibroblasts cell line NIH3T3 and enhance the cell susceptibility to transformation. Compared with wild‐type cells, ATG5 KO cells had stronger migration ability and significantly increased resistance to the Src tyrosine kinase inhibitor PP2 . The results showed that autophagy deficiency can induce malignant cell transformation and resistance to PP2.…”
Section: Using Crispr/cas9 In the Study Of Tumor Therapiesmentioning
confidence: 94%
See 1 more Smart Citation
“…The use of CRISPR/Cas9‐mediated ATG5 knockout can significantly promote cell proliferation of the mouse embryonic fibroblasts cell line NIH3T3 and enhance the cell susceptibility to transformation. Compared with wild‐type cells, ATG5 KO cells had stronger migration ability and significantly increased resistance to the Src tyrosine kinase inhibitor PP2 . The results showed that autophagy deficiency can induce malignant cell transformation and resistance to PP2.…”
Section: Using Crispr/cas9 In the Study Of Tumor Therapiesmentioning
confidence: 94%
“…56,88,94,97,100,113,[141][142][143][144][145][146][147][148][149][150][151][152][153][154][155] Compared with wild-type cells, ATG5 KO cells had stronger migration ability and significantly increased resistance to the Src tyrosine kinase inhibitor PP2. 156 The results showed that autophagy deficiency can induce malignant cell transformation and resistance to PP2.…”
Section: Drug Resistance Study Of Tumorsmentioning
confidence: 99%
“…In contrast, other evidence indicates that the predominant role of autophagy in cancer cells is to maintain tumor cell survival (Degenhardt et al 2006). Our previous studies also showed that autophagy could play a dual role in either pro-cell survival or pro-cell death in response to anticancer drugs (Hwang et al 2018).…”
Section: Introductionmentioning
confidence: 89%
“…Autophagy was measured by the conversion of LC3-I to LC3-II by immunoblot analysis as previously (Hwang et al 2018). Detection was achieved using the Bio-Rad ChemiDoc XRS+ instrument (Hercules, CA, USA), and the data were visualized using the Bio-Rad Image Lab software version 5.2.1 (Bio-Rad Laboratories).…”
Section: Autophagy Monitoring Assay By Conversion Of Lc3mentioning
confidence: 99%
See 1 more Smart Citation